(untitled) (Altre Modernità, 2019)
Joseph Conrad’s The Secret Agent (1907) is a novel that reflects Conrad’s ambivalent poetics and allusive style. In this text, psychological analysis does not simply represent the background of the story, but its narrative matrix. However, despite the fact that The Secret Agent would seem, apparently, to be unsuitable for visual adaptation, there have been various TV and cinema translations. Our investigation will prove the novel’s capacity to “adapt” to different historical and cultural contexts. After a brief introduction to other screen afterlives of Conrad’s novel, starting with Alfred Hitchcock’s Sabotage (1936), we will focus on a TV adaptation broadcast on Italy’s national network RAI in 1978. Directed by Antonio Calenda (script by Dante Guardamagna and Franco Vegliani), L’agente segreto was produced in the socalled “Years of Lead” and when the “Strategy of Tension” was at its peak. In this respect, this TV version addressed issues that were cogent during the late-seventies in Italy. Moreover, it is significant that Dante Guardamagna also directed, in the same year, the TV adaptation of Ferdinando Camon’s novel Occidente (1975), which investigated the psyche of a right-wing terrorist.